Research progress of ion exchange selective electrodialysis - HUANG Hanwen; FENG Ling; TIAN Binghui (Gongye shui chuli)
Ion exchange selective electrodialysis(ISED) is a water treatment technique that uses ion exchange resin filling to improve the efficiency of ion separation by electrodialysis under specific conditions. With relatively high energy efficiency and no need for resin acid-base regeneration, ISED has been now used in ultra-pure water preparation and specific wastewater treatment in the electric power, pharmaceutical,automotive and other industries. While distinguishing between ion exchange electrodialysis(IXED) and ISED, this paper comprehensively summarized and discussed the theory, mechanism and model of ion movement and separation of target ions in IXED and ISED processes. On this basis, the development status of IXED and ISED process structures and technologies was summarized, and the research progress of ISED technology in the direction of ion separation and recovery in groundwater and industrial wastewater was discussed and analyzed. Finally, the future development direction of selective salt separation by ISED technology was prospected from three aspects of resin,membrane material and operation mode.